2019
DOI: 10.1155/2019/9051713
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Effect of Hyperbaric Oxygen Therapy Duration on Calvarial Defects in Irradiated Rats

Abstract: Objective. In this study, we evaluated changes in bone remodeling in an irradiated rat calvarial defect model according to duration of hyperbaric oxygen therapy. Materials and Methods. The 28 rats were divided into four groups. Radiation of 12 Gy was applied to the skull, and 5-mm critical size defects were formed on both sides of the skull. Bone grafts were applied to one side of formed defects. From the day after surgery, HBO was applied for 0, 1, and 3 weeks. At 6 weeks after bone graft, experimental sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…Treating osteoblasts with HBOT also improved their proliferation rate compared to hypoxic or normoxic conditions and increased alkaline phosphatase activity (ALP) [ 25 ]. Hyperbaric oxygen relieved radiation-induced osteonecrosis in rats by contrasting the inflamed, hypocellular, hypovascular, and hypoxic environment in the damaged bone and promoting vascularization [ 13 , 14 ]. In patients with AVNFH, hyperbaric oxygen was demonstrated to reduce inflammatory markers such as tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, creating a favorable osteogenic environment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treating osteoblasts with HBOT also improved their proliferation rate compared to hypoxic or normoxic conditions and increased alkaline phosphatase activity (ALP) [ 25 ]. Hyperbaric oxygen relieved radiation-induced osteonecrosis in rats by contrasting the inflamed, hypocellular, hypovascular, and hypoxic environment in the damaged bone and promoting vascularization [ 13 , 14 ]. In patients with AVNFH, hyperbaric oxygen was demonstrated to reduce inflammatory markers such as tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, creating a favorable osteogenic environment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully used in many pathologies characterized by osteonecrosis, such as avascular necrosis of the femoral head (AVNFH) and osteonecrosis of the knee [ 7 , 8 , 9 ]. In particular, referring to the oral and maxillofacial districts, HBOT increased the bone regeneration rate in osteoradionecrosis, mandibular osteomyelitis, and dental implants [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Формирование новой кости напрямую зависит от снабжения тканей кислородом и значительно выше при нормоксических условиях [42]. Положительное влияние гБО на регенерацию тканей доказано экспериментально на животных и в клинической практике [43,44]. гБО кислородом стимулирует процессы остеогенеза при удлинении конечностей, ликвидирует ишемию, развивающуюся в тканях, повышает насыщение их кислородом, улучшает обменные процессы, о чем свидетельствует исчезновение отеков и болевых ощущений [45,46] [39,47,48,49,50,51].…”
Section: способы стимуляции остеогенезаunclassified
“…Several studies in which μCT was used to assess the repair of critical defects have shown that this method confirms and validates histomorphometric findings, besides adding relevant information such as bone mineral density, bone mineral content and bone volume. 26,38,39,[45][46][47][48][49][50] The inclusion of immunohistochemical analysis for bone resorption and neoformation markers in earlier periods of healing could also contribute to the understanding of the biological phenomena that may explain the behavior of demineralized autogenous bone as a graft material.…”
Section: F I G U R Ementioning
confidence: 99%